2020
DOI: 10.3390/ijerph17186730
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Mental Health Disorders among Rohingya Refugees: A Malaysian Perspective

Abstract: Mental health disorders (MHDs) among refugees has been recognized as a major public health issue. However, to date, there is limited evidence on the prevalence of MHDs among Rohingya refugees in Malaysia. This study aimed to examine the prevalence and associated factors of major depressive disorder (MDD), generalized anxiety disorder (GAD), and post-traumatic stress disorder (PTSD) among Rohingya refugees in Malaysia. A total of 220 refugees were randomly selected to participate in this cross-sectional study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 63 publications
2
40
0
Order By: Relevance
“…Similar results found that a lack of social support was associated with poorer mental health. 39 , 40 , 41 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results found that a lack of social support was associated with poorer mental health. 39 , 40 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that male refugees had a higher prevalence of poor mental health. 38 , 41 , 42 A qualitative study among refugees from Afghanistan speculates that the lack of job opportunities plays a crucial role in mental distress among men after years of forced migration. 43 Rohingya women do not get enough paid jobs in conservative Rohingya society, making it difficult for them to earn a living.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found higher DS in older adults female Rohingya FDMNs as compared to their male counterparts and this corroborates with previous findings in Rohingya FDMNs in Bangladesh (Turrini et al ., 2017 ), Rohingya FDMNs in Malaysia (Kaur et al ., 2020 ), Syrian refugees in Iraq (Mahmood et al ., 2019 ) and Bosnian refugees in Sweden (Blight et al ., 2006 ). It is evident from both local and global evidence that refugees have disproportionate outcomes based on gender and females suffer more psychosocial trauma, indicating the influence of both psychosocial and biological factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the second one [ 10 ], the researchers analysed how the characteristics of the neighbourhood can influence poor mental health and how it is necessary to take them into account to develop national policies and programmes that influence and improve the health of residents. Another article analysed protective and risk factors for the mental health of Rohingya refugees [ 11 ]. This study concluded that violence, food insecurity, and low social support significantly increase the odds of mental health diseases, and more efforts are needed to address these issues.…”
Section: Resultsmentioning
confidence: 99%